Criminalising women rapist in Malaysia / Farzana Alias … [et al.] - Alias, Farzana; Azizor Rahman, Nur Shainaz; Roslan, Ros Syamimi; Yang Mohsin, Wan Mastura (2014)
This research paper is carried out to amend Section 375 of the Penal Code and thus criminalize the women rapist in Malaysia with references to United States, United Kingdom and Russian legislation. Rape is a sexual offence under the criminal law that profound to be affecting every society and known by worldwide range. This sexual conduct on woman rapist is no longer bizarre as there is evidence that male rape victims suffered the same physical, psychology and emotional hurts likewise the woman victims. Nevertheless, in other developed country such as the United States, United Kingdom and Russia, they had already amend their legislation on the definition of rape by inserting circumstances whereby male rape are also to be considered as one of possible victim. In Malaysia, the legislation that is still in force and applies to rape cases yet to remain the same without any amendment or alteration. The provision of rape in the Malaysian Penal Code is inadequate to curb the problem in male rape cases where concerns on the protection of the male victims. Even though there are limited reported cases on male rape in Malaysia, there might be in future of such cases to occur align with our modern society development. As consequence, the authority might be facing problems to classify under which provisions this male rape cases falls into. Accordingly, this research paper demonstrates the effectiveness of United States, United Kingdom and Russian legislation to deal with the male rape cases.